India : Financial System Stability Assessment-Press Release and Statement by the Executive Director for India. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses the findings of the Financial System Stability Assessment for India. Since the 2011 Financial Sector Assessment Program, India has recorded strong growth in both economic activity and financial assets, supported by important structural reforms and terms of trade gains. Increased diversification, commercial orientation, and technology-driven inclusion have supported growth in the financial industry, backed by improved legal, regulatory, and supervisory frameworks. Yet, the financial sector is facing considerable challenges, and economic growth has recently slowed down. High nonperforming assets (NPAs) and slow deleveraging and repair of corporate balance sheets are testing the resilience of the banking system, and holding back investment and growth. The authorities have been pursuing policies to accelerate the process of NPA resolution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet